2014
DOI: 10.1097/mib.0000000000000210
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Intestinal T Helper Cell Profiling Reveals Specific Accumulation of IFN-γ+IL-17+Coproducing CD4+ T Cells in Active Inflammatory Bowel Disease

Abstract: Our results argue against the controversial TH1/TH2 or TH17/Treg paradigms. In contrast, they suggest that a subpopulation of TH17 cells sharing a TH1 signature may be specifically involved in intestinal inflammation in CD and UC. These findings provide a better understanding of IBD pathogenesis and may help explain the efficacy of anti-IL-12p40/IL-23 and failure of anti-IL-17A therapies despite the enrichment of TH17 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 39 publications
3
96
0
4
Order By: Relevance
“…Interestingly, CD14 + macrophages can induce a T-cell population producing IFNγ and IL-17 in vitro. Consistently, an IFNγ + IL-17 + T-cell population was observed in the intestinal mucosa of CD patients [90]. As for the plasticity in the T-cell development, this double-positive T-cell population is thought to differ from Th17 cells [91].…”
Section: Crohn's Diseasementioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, CD14 + macrophages can induce a T-cell population producing IFNγ and IL-17 in vitro. Consistently, an IFNγ + IL-17 + T-cell population was observed in the intestinal mucosa of CD patients [90]. As for the plasticity in the T-cell development, this double-positive T-cell population is thought to differ from Th17 cells [91].…”
Section: Crohn's Diseasementioning
confidence: 74%
“…Like in CD, IL-23 from CD14 + CD68 + macrophages promote Th17-cell immune responses crucially contributing to the chronic local inflammation of UC [135,136]. Additionally, the T-cell population double positive for IFNγ and IL-17 and originating from Th17 cells is not specific for CD but also present in the intestinal mucosa of patients with active UC [90]. …”
Section: Ulcerative Colitismentioning
confidence: 99%
“…T cells. This dual Th1 and Th17 phenotype drives autoimmune pathology, suggesting a key role for infiltrating DC in the pathogenesis of these diseases [64,152,153]. DC derived from human inflammatory tissues express CD1a, CD1c, FceR1, CD206, CD14, CD11b, M-CSFR and ZBTB46 [64].…”
Section: Inflammatory DCmentioning
confidence: 99%
“…Th17.1 cells which express chemokine receptors; CXCR3, CCR6: C-type lectin; CD161: and IL-23R (Annunziato et al, 2007, Nistala andWedderburn, 2009), and have been identified in arthritic patients (Cosmi et al, 2008, Maggi et al, 2014, Nistala and Wedderburn, 2009), CD patients (Annunziato et al, 2007, Ramesh et al, 2014, IBD patients (Globig et al, 2014), and AS patients (Limon-Camacho et al, 2012, Zhang et al, 2012. Th17.1 phenotype can be distinguished from classical, memory Th1 cells based on the expression of CD161, where it is not expressed on Th1 cells (Annunziato et al, 2013, Cosmi et al, 2008.…”
Section: 6) Memory Th171 Cells -Phenotypementioning
confidence: 99%